Influence of Castor Oil on Glycated Hemoglobin (HbA1c) on Induced Type 2 Diabetes Mellitus in Rats - Abu Dayyih, Wael; Manaysa, Mohamad; Hailat, Mohammad; Zakareia, Zainab; El Hajji, Feras (Jordan Journal of Pharmaceutical Sciences, 2021)
Many T2D use CAO as a laxative. We did not find sufficient research to explain CAO's potential effect on the levels of HbA1c in T2D patients. This study will study this effect. Rats (n=80) were divided into eight groups (n=10). Five groups (n=50) were injected with streptozotocin intravenously to induce T2D. One group was given CAO with empagliflozin, and the second was assigned CAO only daily. The third was assigned CAO every two days, with empagliflozin, which was given daily. A fourth was assigned CAO alone daily. Also, the fifth was given empagliflozin alone. In the healthy groups, one group was given CAO, and the other was given empagliflozin. Also, the last healthy group was not assigned any drug. CAO's result on HbA1c in healthy rats was noted to decrease when delivered alone for eight weeks. HbA1c of the diabetic groups showed no significant difference (P-value<0.05) when comparing the rats given CAO with empagliflozin, and the rats were given CAO only. There was also no noticeable effect among the groups of rats given CAO daily and every two days. This study explains that CAO does not lead to a significant difference in HbA1c levels in diabetic rats, even it did for healthy rats, and if given alone, CAO could affect HbA1c levels if given over a long period. Also, CAO has a noticeable impact on experimental rats that co-administered Empagliflozin on HbA1c levels, and that Empagliflozin effect is not significantly affected if taken with CAO.